Identidade e diferença nas altas habilidades/ superdotação (AH/SD): uma análise de conteúdo - Terra, Eliane Cinira Rodrigues (2022)
According to studies made by the World Health Organization (WHO) around 3.5% to 5.0% of the Brazilian population has High Abilities/Giftness (AH/SD), according to Freitas and Rech (2005). However, when unveiling the current school context with the search for quantitative data collected with SEED/PR and on the MEC’s official website, it is clear that a considerable portion of students remains without proper identification of their potential. Therefore, it can be said that these students are not receiving adequate stimuli in the education system to develop their potential. However, according to the National Policy on Special Education from the Perspective of Inclusive Education (MEC, 2008) the AH/SD are part of the target audience of Special Education. This educational policy affirms the importance of identifying this population during the educational process. In this regard, Vieira (2018) states that there is significant misinformation about this portion of the population in the school context. Therefore the differences and specificities presented by gifted students need to be considered in the inclusive context só that their educational process can be properly carried out. It is noteworthy that the identity and difference of people with AH/SD, being constituted in social and cultural relationships, are reflected in institutional educational spaces, in which inclusion and special education can promote the learning process of these students. Presenting aspects related to identity and difference, this theme requires the revision and resignification of concepts, concomitant with the deconstruction of myths. This will directly affect the recognition and identification of these subjects in the educational context. Starting from the premise that culture is the basis for identity and difference, and that the identification of students with AH/SD is relevant to the educational process, the objective of this research is to analyze in official documents of the Brazilian federal government how they are permeated the values of identity and difference of students with AH/SD. With a documental research approach carried out in official Brazilian documents, data are sought for subsequent content analysis with the following steps: pre-analysis, coding, categorization, and interpretation. In this bias, this dissertation carried out with the purpose of applied research, permeates and integrates knowledge relevant to identity and difference, identification, history, inclusion, public policies and actions aimed at promoting the learning potential of gifted students. By analyzing in these documents the counterpoint between Inclusion and Special Education, quantitative and qualitative data that support and determine the educational actions for these students are investigated through content analysis.